Layer‐Tunable Phosphorene Modulated by the Cation Insertion Rate as a Sodium‐Storage Anode. Issue 34 (10th July 2017) - Huang, Zhaodong; Hou, Hongshuai; Zhang, Yan; Wang, Chao; Qiu, Xiaoqing; Ji, Xiaobo
Abstract : Liquid phase exfoliation of few‐layer phosphorene (FL‐P) is extensively explored in recent years. Nevertheless, their deficiencies such as ultralong sonication time, limited flake size distribution, and uncontrollable thicknesses are major hurdles for the development of phosphorene‐based materials. Herein, electrochemical cationic intercalation has been introduced to prepare phosphorene, through which large‐area FL‐P without surface functional groups can be efficiently attained (less than 1 h). More importantly, its layer number (from 2 to 11 layers) can be manipulated by changing the applied potential. The as‐obtained phosphorene delivers superior sodium‐storage performances when directly utilized as an anode material in sodium‐ion batteries. This electrochemical cation insertion method to prepare phosphorene should greatly facilitate the development of phosphorene‐based technologies. Moreover, this work provides the possibility for the scalable preparation of monolayer 2D materials by exploring intercalation ions. Additionally, the successful electrochemical exfoliation of phosphorene can promote the application of electrochemical exfoliation in other 2D materials. Abstract : Large‐area phosphorene is efficiently obtained through electrochemical cationic intercalation and the number of phosphorene layers is manipulated by the cation insertion rate. This material delivers superior sodium‐storage performance when serving as a sodium‐storage anode.